Respuesta :
Answer:
even
Step-by-step explanation:
f(-x)=f(x) means f is even
f(-x)=-f(x) means f is odd
If you get neither f(x) or -f(x), you just say it is neither.
f(x)=x^4+7x^2-30
f(-x)=(-x)^4+7(-x)^2-30
f(-x)=x^4+7x^2-30
f(-x)=f(x)
so f is even.
Notes:
(-x)^even=x^even
(-x)^odd=-(x^odd)
Examples (-x)^88=x^88 and (-x)^85=-(x^85)
Answer: even
Step-by-step explanation:
By definition a function is even if and only if it is fulfilled that:
[tex]f(-x) = f(x)[/tex]
By definition, a function is odd if and only if it is true that:
[tex]f (-x) = -f(x)[/tex]
Then we must prove the parity for the function: [tex]f(x) = x^4 + 7x^2 - 30[/tex]
[tex]f(-x) = (-x)^4 + 7(-x)^2 - 30[/tex]
[tex]f(-x) = x^4 + 7x^2 - 30=f(x)[/tex]
Note that for this case it is true that: [tex]f(-x) = f(x)[/tex]
Finally the function is even